PTEN self-regulates through USP11 via the PI3K-FOXO pathway to stabilize tumor suppression - Park, Mi Kyung; Yao, Yixin; Xia, Weiya; Setijono, Stephanie Rebecca; Kim, Jae Hwan; Vila, Isabelle K.; Chiu, Hui-Hsuan; Wu, Yun; Billalabeitia, Enrique González; Lee, Min Gyu; Kalb, Robert G.; Hung, Mien-Chie; et al. (Nature communications, 2019)
PTEN is a lipid phosphatase that antagonizes the PI3K/AKT pathway and is recognized as a major dose-dependent tumor suppressor. The cellular mechanisms that control PTEN levels therefore offer potential routes to therapy, but these are as yet poorly defined. Here we demonstrate that PTEN plays an unexpected role in regulating its own stability through the transcriptional upregulation of the deubiquitinase USP11 by the PI3K/FOXO pathway, and further show that this feedforward mechanism is implicated in its tumor-suppressive role, as mice lacking Usp11 display increased susceptibility to PTEN-dependent tumor initiation, growth and metastasis. Notably, USP11 is downregulated in cancer patients, and correlates with PTEN expression and FOXO nuclear localization. Our findings therefore demonstrate that PTEN-PI3K-FOXO-USP11 constitute the regulatory feedforward loop that improves the stability and tumor suppressive activity of PTEN. PTEN is a lipid phosphatase that functions as a dose-dependent tumor suppressor through the PI3K/AKT pathway. Here the authors describe a signaling feedback mechanism where PTEN stability is regulated through transcriptional upregulation of X-linked ubiquitin-specific protease 11 (USP11) via the PI3K/FOXO pathway.